A PWM DC-DC converter with optimum segmented output stage and current detector. Issue 8 (August 2015) - Luo, Ping; Bai, Chunlei; Zhou, Caiqiang; Luo, Ming
Abstract High efficiency is very important for DC-DC power supplies in portable applications. A PWM DC-DC converter with optimum segmented output stage is proposed in this paper whose efficiency at light load is improved. The segmented output stage is optimally divided into 5 small segments plus 4 big segments. The segmented number of the output stage can be adaptively regulated according to the load current. Moreover, two current detector circuits are simultaneously adopted to form a mixed load current sensor in the converter to improve the detecting accuracy. A segmented current SenseFET (SCS) is used to sense the load current in continuous current mode, and a time digital converter with digital judgement (TDC-D) is designed to detect the load current in discontinuous current mode. The structure of the proposed PWM converter with optimum segmented output stage and mixed load current detector circuits is described in this paper, which has been implemented in a 0.13 μm CMOS process. Simulation and testing results show that the output stages of the PWM converter can self transit from one segment stage to another segment stage according to the load condition. And the maximum efficiency improvement of the proposed converter can reach 15%.